Analysis of Cheating in Exams Based on Difference Equation Model. Issue 1 (April 2021) - Wu, Chaolin; Maalla, Allam
Abstract: The problem of cheating in exams is a serious social problem, and cheaters have done huge damage to the social public order. How to reduce or even eliminate cheaters? Researchers have analyzed from different angles, most of the research is from the perspective of game theory or evolutionary game theory. However, game theory and evolutionary game theory have the disadvantage of not being able to quantitatively examine the changes in the number of cheaters and supervision. Aiming at the deficiencies of game theory and evolutionary game theory, this paper establishes the evolution model of the cheating problem of the differential equation model, analyzes the balance point and characteristics of the coexistence evolution model of different actors of cheaters and regulators, and examines the behavior of cheaters along with supervision. Changes in the number; the influence of different factors on the changes in the number of cheaters is analyzed, and on this basis, a comparison of anti-cheating strategies is made. After comparing the effects of the two different anti-cheating strategies of 'blocking' and 'blocking', it is concluded that 'blocking' can reduce cheaters more than 'blocking', and corresponding policy recommendations are given. Considering that it is difficult to obtain the data of cheaters and supervisory behaviors, the model was simulated using MATLAB, and the simulation results verified the correctness of the analysis.